Reaktualisasi Strategi Pendidikan Islam: Ikhtiar Mengimbangi Pendidikan Global - M. Sobry (Ulumuna, 2014)
Globalization is inevitable phenomenon that may cause anxiety amongst countries, such as Indonesia, that still preserve their culture, ethics and religious values because it always introduces new things that are not easily adjusted to regional or local contexts. Globalization as it is reflected in rapid change and transformation in technology has affected most of human’s life, including education. Globalized education is the one that is characterized by global and transnational elements in its basic structure, for example, the use of information technologies and digital media that have both positive and negative impacts. However, for Indonesia, whose majority population is Islam, globalization is not a threat, which should be evaded. What needs to do is to integrate Islamic concepts and values in it. Globalization and its type of education that looks contrary to religious norms will no longer become a menace if it is strengthened with religious values.